Recruiting women to vascular surgery and other surgical specialties - Dageforde, Leigh Anne; Kibbe, Melina; Jackson, Gretchen Purcell (Journal of vascular surgery, 2013)
Vascular surgery is a subspecialty that attracts future surgeons with challenging technical procedures and complex decision making. Despite its appeal, continued promotion of the field is necessary to recruit and retain the best and brightest candidates. Recruitment of medical students and residents may be limited by the lifestyle inherent to vascular surgery and the length of residency training. The young adults of the current applicant and resident pool differ from prior generations in their desire for hands-on mentoring, aspirations to affect change daily, a penchant for technology, and strong emphasis on work-life balance. Furthermore, the percentage of women pursuing careers in vascular surgery is not representative of the eligible workforce. Women are now the majority of graduates in all of higher education, and thus, vascular surgery may need to make a concerted effort to appeal to women in order to attract the most talented young professionals to the field. Recruiting strategies for both men and women of Generation Y should target a diverse group of potential candidates with an awareness of the unique characteristics and needs of this generation of rising surgeons.